DESIGN AND SIMULATION OF WALL-CROSS DETECTION SECURITY SYSTEM USING PIC16F877A MICROCONTROLLER - AHMAD, MUHAMMAD BABALLE (Fırat Üniveristesi, 2018)
Günümüz dünyası son derece entegre ve özellikle dijital menkul kıymetlere, haberleşmelere vb. Bağlı olarak dijital elektroniğe dayanıyor. Kuzey duvarı, güney duvarı, doğu duvarı ve batı duvarı dört kare duvarın arkasına bakmak için bir güvenlik sistemi geliştirildi. Her duvarın, ışığa bağımlı direnç (LDR) ve ışık yayan diyot (LED) kullanılarak tasarlanan bir sensörü vardır. periferik arabirim denetleyicisi 0 volt algıladığında, çevresel voltaja (LDR) 0 volt'u periferik arabirim denetleyicisine (teçhizatın beyni olarak çevresel arabirim denetleyicisi işlevi) vermek için 0 volt çıkışa dönüştürür ve bunu görüntülemek için sıvı kristal ekrana (LCD) sinyal gönderir. Bu duvar geçildi ve sistem gerçek zamanlı bir video yakalamak ve sesli uyarı göndermek için kapalı devre televizyon (CCTV) kamerasını çapraz duvarda durmak üzere taşıyan dc motoru hemen döndürecektir. Periferik arabirim denetleyicisi (PIC) tüm duvarlardan ışık bağımlı dirençten (LDR) 5 volt algılarsa, tüm duvarların çaprazlanmaması anlamına gelir, tüm duvar ışığına bağımlı direnç (LDR) çıkışı 5 volt çevresel arabirim denetleyicisi (PIC) ) sıvı kristal ekran (LCD) "tüm duvarlar ok" da görüntülenecektir. Sistem ayrıca sıvı kristal ekran (LCD) üzerinde bir takvim (saat ve tarih) görüntüler.

The world of today is highly integrated and depends on digital electronics especially in securities, communications, etc. in this thesis a security system was developed to look after four square walls north wall, south wall, east wall and west wall. Each wall has a sensor designed using light dependent resistor(LDR) and light emitting diode(LED) whenever somebody or something crossed the wall he/she blocked the light-dependent resistor(LDR) from receiving light from light emitting diode(LED) that makes the light dependent resistor(LDR) to output 0 volt to peripheral interface controller (the peripheral interface controller function as the brain of the thesis) whenever the peripheral interface controller detects 0 volt it send signal to liquid crystal display(LCD) to display that, that particular wall has been crossed, and the system will immediately rotate the dc motor that carries closed-circuit television(CCTV) camera to stop at the crossed wall in order to capture a real-time video and send to the buzzer. If the peripheral interface controller(PIC) detects 5 volts from all the walls light dependent resistor(LDR) that means that all the walls are not being crossed, if all wall light dependent resistor(LDR) output 5 volts the peripheral interface controller(PIC) will display on the liquid crystal display(LCD) "all walls ok". The system also displays a calendar (time and date) on liquid crystal display(LCD).
Pİc16f877a mikrodenetleyici kullanarak duvar-çapraz saptanım güvenlik sisteminin tasarımı ve simülasyonu
Keywords: Mekatronik Mühendisliği